ANIMALS IN RESOCIALIZATION - Czerw, Monika (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The benefits of relations between humans and animals have encouraged both scientists and members of other communities to popularize the knowledge in the field of animal-assisted therapy. Currently, animal-assisted therapy has been used not only in therapy, but also in resocialization. The increasing popularity of this form of supporting maladjusted people who are isolated from society or people with disabilities encouraged both practitioners and researchers to organize knowledge, thus reducing the scepticism about the usefulness of animal-assisted therapy. In Poland, the particular focus of the animal-assisted therapy is on the use of dogs to enhance the resocialization process. However, various experimental resocialization programs have also used horses and even lamas. This paper is intended to familiarize the reader with the aspects of the assistance of animals in resocialization. Furthermore, it emphasizes the difficulties and advantages that can be expected from integration of this type of therapy into resocialization programs.